Oxford international primary English student book for grade 5 - Barber, Alison (Karachi : Oxford university press, 2022)
"Oxford International Lower Primary English Student Book (Grade 5)" is a comprehensive and engaging English language textbook designed for Grade 5 students. The book is part of an international curriculum and aims to develop essential language skills, including reading, writing, speaking, listening, grammar, and vocabulary, through interactive and structured content.
Keywords: English : Textbook; Oxford : Garde 5